The impact of brand extension on brand image (Case study: Tak Makaroon and Pegah companies) - . Abolfazl Tajzadeh Namin; Fatemeh Chehraqi; Aidin Tajzadeh Namin (مطالعات مدیریت بهبود و تحول, 2011)
Brand extension strategies will increase the likehood success of new products, while deducts the risks of brand image dilution. This study analyzes how brand extension impacts on brand image. Research model includes six variables: initial brand image, brand extension attitude, category fit, brand image fit, final brand image and consumers innovativeness. The current study is a descriptive- survey one, from the reseach approach and the population consists of the customers of Peghah and Tak Makaroons' products in Ghazvin city. The cluster sampling is used in this study. The questionnaires were distributed among the available customers of groceries in Ghazvin city. Respectively, 298 and 300 questionnaires were collected from customers of Peghah and Tak Makaroon's products. The Results of Beta Coefficient shows that in both Peghah and Tak Makaroon companies, the initial brand image has the most impact on brand extension attitude as well as final brand image of new products. However the relevant impact on Peghah company is more than Tak Makaroon firm.